Pengaruh Earning Presure Dan Leverage Terhadap Konservatisme Akutansi: Studi Kasus Pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2019 - Rasfiuddin Sabaruddin; Azhar Affandi (Prodi Akuntansi STIE Hidayatullah Depok, 2021)
This study aims to determine the effect of Earning Presure and Leverage on Accounting Conservatism in Manufacturing Companies in the Consumer Goods Industry Sector that are Listed on the IDX. The method used is explanatory research with analysis techniques using statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study Earning Presure has no significant effect on Accounting Conservatism by testing the hypothesis obtained t count <t table or (-0.367 <1.994). Leverage has a significant effect on accounting conservatism by testing the hypothesis obtained t count> t table or (4.124> 1.994). Earning Presure and Leverage simultaneously have a significant effect on Accounting Conservatism with the regression equation Y = -0,354 - 0,122X1 + 0,448X2 and the influence contribution is 24,9%, the hypothesis test obtained F count> F table or (7,278> 2,740).